Analysis of the evaluation of investment projects with constant prices versus current prices approaches - José Asunción Corona Due\~nas; César Corona Pacheco (Atlantic Review of Economics (ARoEc), 2021)
This work makes a comparative analysis of the evaluation of an investment project, considering two approaches, one with cash flows at constant prices and the other at current prices. The goal is to determine which of these two approaches is best for project evaluation to make the right investment decision. At present, both positions remain, as some authors recommend that the best approach to evaluate investment projects is to use cash flows at current prices, while others prefer the constant prices approach. The study presented here performs an analysis of the growth of these flows considering an increase in real production in both approaches at constant and current prices, and the project is evaluated using two methods: NPV and IRR. With the results obtained, a discussion is carried out where it is shown that the main conclusion is that the constant prices approach is better for evaluating investment projects and determining their viability without incurring additional risks to the project.
Keywords: E31; G24; G31; G32; 330; Investment Projects; Evaluation of Investment Projects; Cash Flows